Genetics of Obesity Traits: A Bivariate Genome-Wide Association Analysis - Wu, Yili; Duan, Haiping; Tian, Xiaocao; Xu, Chunsheng; Wang, Weijing; Jiang, Wenjie; Pang, Zengchang; Zhang, Dongfeng; Tan, Qihua (Frontiers in Genetics, 2018)
Previous genome-wide association studies on anthropometric measurements have identified more than 100 related loci, but only a small portion of heritability in obesity was explained. Here we present a bivariate twin study to look for the genetic variants associated with body mass index and waist-hip ratio, and to explore the obesity-related pathways in Northern Han Chinese. Cholesky decomposition model for 242 monozygotic and 140 dizygotic twin pairs indicated a moderate genetic correlation (r=0.53, 95%CI: 0.42-0.64) between body mass index and waist-hip ratio. Bivariate genome-wide association analysis in 139 dizygotic twin pairs identified 26 associated SNPs with p < 10-5. Further gene-based analysis found 291 nominally associated genes (P<0.05), including F12, HCRTR1, PHOSPHO1, DOCK2, DOCK6, DGKB, GLP1R, TRHR, MMP1, GPR55, CCK and OR2AK2, as well as 6 enriched gene-sets with FDR<0.05. Expression quantitative trait loci analysis identified rs2242044 as a significant cis-eQTL in both the normal adipose-subcutaneous (P=1.7×10-9) and adipose-visceral (P=4.4×10-15) tissue. These findings may provide an important entry point to unravel genetic pleiotropy in obesity traits.